2022
DOI: 10.3390/w14030317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Freezing–Thawing on Dynamic Properties of Loess Reinforced with Polypropylene Fiber and Fly Ash

Abstract: Periodic freezing–thawing is recognized as a real threat to the mechanical properties of reinforced loess, which has been used in the recent construction of high-speed railways in northwest China; however, the performance of these materials under periodic freezing–thawing and dynamic loading has rarely been investigated. In this work, dynamic triaxial tests were conducted on fly ash- and polypropylene fiber-reinforced loess with different blend ratios and freeze–thaw cycles. The dynamic shear modulus and dampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Su and Lei 39 pointed out that palm fiber can remarkably improve UCS of loess, and the influence of dry density on strength is significant, while the impact of FL is not significant. Chen et al 40 declared that the dynamic shear modulus of loess enlarged remarkably with raising fly ash content and cell pressure, whereas the damping ratio decreased as increasing fly ash content and σ 3 . Yang et al 41 found that the polypropylene fibers can change the cement-modified loess from brittle to plastic damage, and the fibers played a bridging role.…”
Section: Introductionmentioning
confidence: 99%
“…Su and Lei 39 pointed out that palm fiber can remarkably improve UCS of loess, and the influence of dry density on strength is significant, while the impact of FL is not significant. Chen et al 40 declared that the dynamic shear modulus of loess enlarged remarkably with raising fly ash content and cell pressure, whereas the damping ratio decreased as increasing fly ash content and σ 3 . Yang et al 41 found that the polypropylene fibers can change the cement-modified loess from brittle to plastic damage, and the fibers played a bridging role.…”
Section: Introductionmentioning
confidence: 99%
“…Su and Lei 18 pointed out that palm ber can remarkably improve UCS of loess, and the in uence of dry density on strength is signi cant, while the impact of FL is not signi cant. Chen et al 19 declared that the dynamic shear modulus of loess enlarged remarkably with raising y ash content and cell pressure, whereas the damping ratio decreased as increasing y ash content and σ 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many scholars have investigated the effects of various factors on the degradation mechanism of soil mechanic properties under a cyclic freeze-thaw action and have constantly tried to improve soil under freeze-thaw cycles [17,18]. The influence factors under investigation were of two types: environmental factors, which mainly included the number of freeze-thaw cycles, amplitude, and freeze-thaw temperature; and the soil's physical indices, such as moisture content and density.…”
Section: Introductionmentioning
confidence: 99%